Antagonizing Arachidonic Acid-Derived Eicosanoids Reduces Inflammatory Th17 and Th1 Cell-Mediated Inflammation and Colitis Severity - Jennifer M. Monk; Harmony F. Turk; Yang-Yi Fan; Evelyn Callaway; Brad Weeks; Peiying Yang; David N. McMurray; Robert S. Chapkin (Mediators of Inflammation)
During colitis, activation of two inflammatory T cell subsets, Th17 and Th1 cells, promotes ongoing intestinal inflammatory responses. n-6 polyunsaturated fatty acid- (PUFA-) derived eicosanoids, such as prostaglandin E2 (PGE2), promote Th17 cell-mediated inflammation, while n-3 PUFA antagonize both Th17 and Th1 cells and suppress PGE2 levels. We utilized two genetic mouse models, which differentially antagonize PGE2 levels, to examine the effect on Th17 cells and disease outcomes in trinitrobenzene sulfonic acid- (TNBS-) induced colitis. Fat-1 mice contain the ω3 desaturase gene from C. elegans and synthesize n-3 PUFA de novo, thereby reducing the biosynthesis of n-6 PUFA-derived eicosanoids. In contrast, Fads1 Null mice contain a disrupted Δ5 desaturase gene and produce lower levels of n-6 PUFA-derived eicosanoids. Compared to Wt littermates, Fat-1 and Fads1 Null mice exhibited a similar colitic phenotype characterized by reduced colonic mucosal inflammatory eicosanoid levels and mRNA expression of Th17 cell markers (IL-17A, RORγτ, and IL-23), decreased percentages of Th17 cells and, improved colon injury scores (P≤0.05). Thus, during colitis, similar outcomes were obtained in two genetically distinct models, both of which antagonize PGE2 levels via different mechanisms. Our data highlight the critical impact of n-6 PUFA-derived eicosanoids in the promotion of Th17 cell-mediated colonic inflammation.